Предмет: Алгебра, автор: marinakrav

Выполните действие
2a(3a-b+4)
Решите уравнение
5(х-3)=14-2(7-2х)
Упростите выражение
6а(а-х+с)+6х(а+х-с)-6с(а-х-с)

Ответы

Автор ответа: karamushevanast
0
1)=6а²-2аb+8
2)5x-15=14-14+4x
5x-4x=15
x=15
3)=6a²-6ax+6ac+6xa+6x²+6xc-6ac+6xc+6c²(-6ax и +6ах, 6ас и -6ас,6ах и -6 ах взаимно уничтожаются)=6а²+6х²+6с²=6(а²+х²+с²)
Автор ответа: aliaqa
0
6a^2-6ax+6ac+6ax+6x^2-6xc-6ac+6cx+6c^2=6a^2+6^2+6c^2
=5x-15-14+14-4x=-9x-15
Автор ответа: aliaqa
0
=x-15
Автор ответа: marinakrav
0
всмысле??
Похожие вопросы